Sex-specific analysis in Behçet's disease reveals higher genetic risk in male patients. Issue 132 (October 2022) - Jo, Yun Gun; Ortiz-Fernández, Lourdes; Coit, Patrick; Yilmaz, Vuslat; Yentür, Sibel P.; Alibaz-Oner, Fatma; Aksu, Kenan; Erken, Eren; Düzgün, Nursen; Keser, Gokhan; Cefle, Ayse; Yazici, Ayten; et al.
Abstract: Objectives: Behçet's disease tends to be more severe in men than women. This study was undertaken to investigate sex-specific genetic effects in Behçet's disease. Methods: A total of 1762 male and 1216 female patients with Behçet's disease from six diverse populations were studied, with the majority of patients of Turkish origin. Genotyping was performed using an Infinium ImmunoArray-24 BeadChip, or extracted from available genotyping data. Following imputation and extensive quality control measures, genome-wide association analysis was performed comparing male to female patients in the Turkish cohort, followed by a meta-analysis of significant results in all six populations. In addition, a weighted genetic risk score for Behçet's disease was calculated and compared between male and female patients. Results: Genetic association analysis comparing male to female patients with Behçet's disease from Turkey revealed an association with male sex in HLA-B / MICA within the HLA region with a GWAS level of significance (rs2848712, OR = 1.46, P = 1.22 × 10 −8 ). Meta-analysis of the effect in rs2848712 across six populations confirmed these results. Genetic risk score for Behçet's disease was significantly higher in male compared to female patients from Turkey. Higher genetic risk for Behçet's disease was observed in male patients in HLA-B / MICA (rs116799036, OR = 1.45, P = 1.95 × 10 −8 ), HLA-C (rs12525170, OR = 1.46, P = 5.66 × 10 −7 ), and KLRC4 (rs2617170, OR = 1.20, P = 0.019). In contrast, IFNGR1 (rs4896243, OR = 0.86, P = 0.011) was shown to confer higher genetic risk in female patients. Conclusions: Male patients with Behçet's disease are characterized by higher genetic risk compared to female patients. This genetic difference, primarily derived from our Turkish cohort, is largely explained by risk within the HLA region. These data suggest that genetic factors might contribute to differences in disease presentation between men and women with Behçet's disease. Highlights: Male patients with Behçet's disease have a higher disease genetic risk. Genetic risk within the HLA class I region was higher in male compared to female patients with Behçet's disease. Sex-specific genetic bias might influence disease presentation in Behçet's disease.